2020
DOI: 10.1093/gji/ggaa382
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fault reactivation on injection-induced dynamic triggering of permeability evolution

Abstract: Summary Mechanisms controlling fracture permeability enhancement during injection-induced and natural dynamic stressing remain unresolved. We explore pressure-driven permeability (k) evolution by step-increasing fluid pressure (p) on near-critically-stressed laboratory fractures in shale and schist as representative of faults in sedimentary reservoirs/seals and basement rocks. Fluid is pulsed through the fracture with successively incremented pressure to first examine sub-reactivation permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The generation and mobilization of rock proppants and rock fragments are the key to understanding the underlying physics of permeability evolution due to the important role they play in the permeability enhancement process in Earth's crust (Candela et al, 2014;Elkhoury et al, 2011) and geo-energy reservoirs (Yildirim et al, 2020;Ji et al, 2022). The effect of cyclic loading on sample crack development can be divided into two parts: Cyclic loading with lower peak stress simply compacts the gaps between rock grains and heals micro-cracks and cleavage planes within rocks (Ghasemi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The generation and mobilization of rock proppants and rock fragments are the key to understanding the underlying physics of permeability evolution due to the important role they play in the permeability enhancement process in Earth's crust (Candela et al, 2014;Elkhoury et al, 2011) and geo-energy reservoirs (Yildirim et al, 2020;Ji et al, 2022). The effect of cyclic loading on sample crack development can be divided into two parts: Cyclic loading with lower peak stress simply compacts the gaps between rock grains and heals micro-cracks and cleavage planes within rocks (Ghasemi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the finite-discrete element numerical simulations and laboratory triaxial experiments have shown that fracturing at meso-scale can result in enhancing localized permeability in tight shales with 0 to 5 orders of magnitude (Hyman et al 2016 ). More complex, dynamic permeability evolution was observed in laboratory experiments of fracture permeability with periods of permeability enhancement induced by hydro-shearing interchanging with periods of slow continuous permeability loss caused by chemo-mechanical compaction during periods of pre- and post-stimulation hold phases (Yildirim et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%